Effect of Weathering on Preservative Treated Finished Wood - Samani, Ajmal; Gupta, Sachin (Indian Forester, 2011)
The effect of weathering on performance of different finishes is evaluated on preservative treated mango wood on the basis of gloss values. Per cent loss in gloss of samples finished with clear varnish is much higher than other finishes applied on preservative treated samples. A comparison of loss in gloss values with and without preservative treatment is also reported. The percent loss of gloss is lowest in the case of linseed oil polished samples.